Effects of diagnostic regions on facial emotion recognition: The moving window technique - Kim, Minhee; Cho, Youngwug; Kim, So-Yeon (Frontiers in Psychology, 2022)
With regard to facial emotion recognition, previous studies found that specific facial regions were attended more in order to identify certain emotions. We investigated whether a preferential search for emotion-specific diagnostic regions could contribute toward the accurate recognition of facial emotions. Twenty-three neurotypical adults performed an emotion recognition task using six basic emotions: anger, disgust, fear, happiness, sadness, and surprise. The participants’ exploration patterns for the faces were measured using the Moving Window Technique (MWT). This technique presented a small window on a blurred face, and the participants explored the face stimuli through a mouse-controlled window in order to recognize the emotions on the face. Our results revealed that, when the participants explored the diagnostic regions for each emotion more frequently, the correct recognition of the emotions occurred at a faster rate. To the best of our knowledge, this current study is the first to present evidence that an exploration of emotion-specific diagnostic regions can predict the reaction time of accurate emotion recognition among neurotypical adults. Such findings can be further applied in the evaluation and/or training (regarding emotion recognition functions) of both typically and atypically developing children with emotion recognition difficulties.